Making a case for combating historical dissociation of the ‘Bushmen’ collection at the Iziko Museums of South Africa - McGinn, Isabelle (University of Pretoria, 2024)
Mini Dissertation (MSocSci (Cultural Heritage Studies: Heritage Conservation))--University of Pretoria, 2023.